Paradigma Berpikir Al-Ghazali: Integrasi Akal, Wahyu, dan Maslahah dalam Menjawab Tantangan Sosial Kontemporer - Setio Budi; Mohammad Mochtar Mas'od (CV Omah Kreator, 2026)
The thought of Imam Al-Ghazali concerning reason and the process of thinking remains an important intellectual legacy within Islamic scholarship, particularly amid the expansion of modern rationalist paradigms that tend to position reason as the primary source of knowledge. This study aims to examine Al-Ghazali's concept of thinking, analyze the position of reason within his framework of Islamic epistemology, and explore the relevance of his thought in addressing contemporary social issues. This research employs a qualitative approach using a library research method. Data were collected from Al-Ghazali's primary works, scholarly journals, books, and other relevant academic sources, which were subsequently analyzed through descriptive-interpretative content analysis. The findings reveal that Al-Ghazali regards reason as an essential instrument for acquiring knowledge and understanding reality; however, its application must be proportional and integrated with revelation, namely the Qur'an and Hadith, particularly in metaphysical and theological matters. Al-Ghazali's criticism of philosophers was not directed toward the existence of reason itself, but rather toward its excessive and autonomous use that neglects the authority of revelation. Furthermore, Al-Ghazali's concept of maslahah remains highly relevant in responding to contemporary social challenges, including economic inequality, the crisis of justice, and corruption practices. Therefore, his thought continues to provide an ethical and epistemological foundation for developing a more just and prosperous society.